A High-Performance and Temperature-Insensitive Shape Sensor Based on DPP-BOTDA - Dexin Ba; Chen Chen; Cheng Fu; Danyang Zhang; Zhiwei Lu; Zhigang Fan; Yongkang Dong (IEEE Photonics Journal)
Distributed optical fiber strain sensing significantly increases the number of sensing points compared with fiber Bragg grating sensor, which makes it an excellent candidate for shape sensing. Theoretical analysis indicates that the spatial resolution of strain measurement is crucial to the performance of shape sensing, so a shape sensor based on differential pulse-width-pair Brillouin optical time-domain analysis is proposed to improve the spatial resolution and shape sensing performance. The sensing fiber is attached on the both sides of a steel strip substrate, which enables the measurement of Brillouin frequency shifts (BFSs) of both the sides to suppress temperature crosstalk. In the experiment, first, the dependence of BFS variation on the curvature of the fiber is measured, the result of which agrees well with theory. Then the reconstruction of three shapes are demonstrated, the spatial resolution of which is 10 cm.